Transcription elongation factor SII interacts with a domain of the large subunit of human RNA polymerase II. - Rappaport, J (1988)
Genomic sequences for the large subunit of human RNA polymerase II corresponding to a part of the fifth exon were inserted into an expression vector at the carboxy-terminal end of the beta-galactosidase gene. The in-frame construct produced a 125-kilodalton fusion protein, containing approximately 10 kilodaltons of the large subunit of RNA polymerase II and 116 kilodaltons of beta-galactosidase. The purified bacterially produced fusion protein inhibited specific transcription from the adenovirus type 2 major late promoter, while beta-galactosidase had no effect. This effect of the fusion protein was during RNA elongation, not at the level of initiation, resembling the faithfully initiated but incomplete transcripts produced with purified factors in the absence of SII. Similarly, monoclonal antibody 2-7B, which reacts with the RNA polymerase II region represented in the fusion protein, inhibited specific transcription at the level of elongation in a whole-cell extract. Both monoclonal antibody 2-7B and the fusion protein, although unable to inhibit purified RNA polymerase II in a nonspecific transcription assay, selectively blocked the stimulation elicited by transcription elongation factor SII on the activity of the purified enzyme in vitro. This suggests that the fusion protein traps the SII in nonstimulatory interactions and that antibody 2-7B inhibits SII binding to RNA polymerase II. Thus, this suggests that an SII-binding contact required for specific RNA elongation resides within the fifth exon region of the largest RNA polymerase II subunit.